2001
DOI: 10.1002/hup.350
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders in Ecstasy (MDMA) users: a literature review focusing on personal predisposition and drug history

Abstract: 3,4-methylenedioxymethamphetamine (MDMA or Ecstasy) has been implicated in the onset of a number of psychological disorders and associated with a number of psychiatric symptoms that have persisted after cessation of the drug. This paper is a review of the published psychiatric case studies from the last 10 years involving MDMA. Only 24% of patients had a previous psychiatric history and 34% had a psychiatric illness amongst first degree relatives. The percentage of patients not having had a personal or family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 26 publications
2
39
0
4
Order By: Relevance
“…Several months later she remained very anxious, emotionally labile and tearful, with frequent panic attacks. Other clinical case studies can be seen in the various reviews (McCann and Ricaurte, 1991;McCann et al, 1996;McGuire, 2000;Schifano et al, 1998;Schifano, 2000;Schifano and Magni, 1994;Soar et al, 2001). The main limitation of using individual abreactions as evidence is that they may be seen as idiosyncratic or atypical.…”
Section: Psychiatric Aspectsmentioning
confidence: 95%
“…Several months later she remained very anxious, emotionally labile and tearful, with frequent panic attacks. Other clinical case studies can be seen in the various reviews (McCann and Ricaurte, 1991;McCann et al, 1996;McGuire, 2000;Schifano et al, 1998;Schifano, 2000;Schifano and Magni, 1994;Soar et al, 2001). The main limitation of using individual abreactions as evidence is that they may be seen as idiosyncratic or atypical.…”
Section: Psychiatric Aspectsmentioning
confidence: 95%
“…A Dutch study reported that MDMA use was proceeded by childhood symptoms of anxiety and depression to a significant degree, and suggested that the euphoric and relaxing effects of MDMA may be particularly seductive in patients thus afflicted [99]. A review of 18 published case reports found that 24% of MDMAexposed mentally ill patients had a psychiatric condition prior to MDMA exposure and that 34% had a significant family history, suggestive of a causative role for MDMA in the remaining individuals [100].…”
Section: Psychiatric Long-term Effectsmentioning
confidence: 99%
“…MacInnes et al [36] debated their finding of heightened depression in some ecstasy users applying a vulnerability model, where prior predisposition made some individuals more susceptible to drug abreactions. Soar et al [47] noted that prior predisposition factors and intensive ecstasy usage patterns could both influence the clinical outcome. Butler and Montgomery [97] suggested that impulsivity was a personality factor of those predisposed to taking illicit drugs, but that regular MDMA usage then intensified this characteristic, possibly via serotonergic neurotoxicity.…”
Section: Nevertheless the Literature Is Clear: Across A Wide Range Ofmentioning
confidence: 99%